Overcoming Institutional and Governance Challenges in Environmental Management : Case Studies from Latin America and the Caribbean Region - World Bank (Washington, DC, 2014)
The Latin America and Caribbean (LAC) region has a unique mix of qualities and challenges when it comes to the environment. It is exceptionally endowed with natural assets, with globally significant biodiversity and valuable crops, and also harbors the world s greatest carbon sink in the Amazon. The purpose of the series is to contribute to the global knowledge exchange on innovation in environmental and water resources management and the pursuit of greener and more inclusive growth. The series addresses issues relevant to the region s environmental sustainability agenda from water resources management to environmental health, natural resource management, biodiversity conservation, environmental policy, pollution management, environmental institutions and governance, ecosystem services, environmental financing, irrigation and climate change and their linkages to development and growth. The author presents three successful case studies. The first case study describes how Colombia designed and implemented an air quality management program based on public awareness, evidence-based policy design, and political commitment to reform. The second case study examines how Brazil is promoting access to environmental justice through the public prosecutors model. A third case study shows how the modeling of climate change and monitoring of glacial retreat in the Andean countries is fostering decision making to address the increasingly important challenge of climate change adaptation.